Bridging Standardization And Adaptation: Implementing The Ummi Method Based On Student Characteristics In Elementary Qur’anic Pedagogy - Albarratut Taqiyah; Zakiyah BZ; Muhammad Kholil (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Conventional Qur’anic instruction in elementary schools often struggles with rigid delivery, student cognitive fatigue, and low recitation accuracy due to a lack of adaptation to children's developmental profiles. This study investigates the implementation of the standardized Ummi Method tailored to student characteristics at MI Miftahul Ulum 01 Bondowoso, examining its pedagogical execution, quality assurance, environmental management, and supporting/inhibiting factors. A qualitative case study design was employed. Data were gathered through extended classroom observations, document analysis, and in-depth interviews with the principal, Ummi coordinator, instructors, and students. Data analysis followed interactive qualitative procedures involving data condensation, presentation, and conclusion drawing. The findings indicate that implementing the Ummi Method through its seven standardized stages, combined with diagnostic placement testing, small-group ratios (10–15 students), and multi-sensory differentiation, significantly improves students' tartil, reading fluency, and tajwid precision. Spatial management—alternating between indoor classrooms and outdoor terraces-effectively mitigates student fatigue. Furthermore, institutional interventions such as the Ummi Clinic and daily Achievement Books successfully resolve domestic practice gaps. Adapting a standardized Qur’anic methodology through differentiated instruction and spatial engineering creates a humanistic, effective learning ecosystem that elevates recitation quality while fostering religious character.